(untitled) (Community Based Medical Journal, 2022)
The Early Screening of Autistic Trait Questionnaire (ESAT) is a tool for detecting the early signs of ASD – as developed by Dietz and colleagues in 2006 as a primary ASD screening checklist (of 14 questions checklist). This is a tested and reliable tool to diagnose early signs of autism in children. The aim of the present study is to determine the prevalence of autistic spectrum disorder by early detection method using the ESAT tool and see its correlation with age difference. This cross-sectional study was conducted between January and December of 2016, in 47 schools of Uttara, Ashulia, Nikujo Area of Dhaka City Corporation and Tongi Area of Gazipur City Corporation under Dhaka Division. A total of 1000 children aged 3-5 years were recruited in the study. The research instrument was a semi-structured questionnaire based on ESAT tool. The mean age of the participants was 4.22±0.709 years or (50.4±8.504) months. The age group 3, 4 and 5 years had 167(16.7%), 451(45.1%) and 382(38.2%) respondents respectively. Of them, a total of 517 were males (51.7%) and 483 were females (48.3%). Most of the respondents were Muslims 966(96.6%), rest are Hindus 32(3.2%) and Christians 2(0.2%). Our study revealed a prevalence of early signs of autism in 2.6% cases (26 in 1000). Among children with ASD, absence of some of those signs (like interest in different sorts of objects; expressed feeling, crying/calling when left alone, liked to be cuddled, spoke a few words or utter various words, and pretending to make a cup of tea using a toy cup and teapot) were related to age difference; the results were statistically significant (P<0.05). CBMJ 2021 January: vol. 10 no. 01 P: 37-42